Penerapan Cara Pembenihan Ikan yang Baik dalam Meningkatkan Kinerja UMKM Pembenihan Udang di Kabupaten Barru, Provinsi Sulawesi Selatan - Sau, Fatimah; Sarma, Ma'mun; Trilaksani, Wini (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2017)
Shrimp is one of the leading commodity of fishery sector in Indonesia because the number of export increasing the foreign exchange for this country. In globalization era, business has fierce competition, so that the quality is a keyword to succeed. Therefore, shrimp hatcheries must be certified. The objectives are to: (1) study the related Good Hatchery Practices (GHP) regulation, (2) Analyze the relationship of application of GHP on shrimp hatchery performances, (3) measure the performance of shrimp hatcheries, (4) identify the Gap of the application of GHP. Content analysis, multiple regression analysis and important-performance analysis (IPA) was used to process the data. Result of content analysis showed that there were no regulation contain the obligation that every farmer must be certified in order to control the seed shrimp quality. Result of multiple regression analysis revealed that the application of GHP had positive impact on shrimp hatchery performances and the most influence factors were food safety and environment. Important-performance analysis showed that the best performance was the availability of adequate production equipment. Average production after applied the GHP principles showed that production increased by 19%. Level of concordance between expectation and performance on hatcheries to meet customer satisfaction and consistency of GHP implementation showed a negative gap value by -1.118, overall performance on hatcheries have not meet customer satisfaction and inconsistent implementing GHP principles